172k views
2 votes
Drag a statement or reason to each box to complete this proof.

this proof -2(x+1)=8, then x= -5

User Samir Adel
by
5.0k points

2 Answers

0 votes

Explanation:

distribute the -2 to (x+1) you end up with -2x-2=8 (multiplication property). Add 2 to both sides to get rid of the -2 of the left (addition property). 8+2=10. -2x=10 divide the -2 to both sides. x=-5 (division property).

User Robosoul
by
5.9k points
3 votes

Answer:

We have to prove that,

-2(x+1)=8, then x= -5

L.H.S.


-2(x+1)=8

By distributive property,


-2x-2=8

Adding 2 both sides ( Additive property of equality )


-2x-2+2=8+2


-2x=10

Divide both sides by -2 ( Division property of equality ),


(-2x)/(-2)=(10)/(-2)


x=-5

= R. H. S

Hence, proved....

User Codingatty
by
6.1k points